STRUCTURAL FEATURES OF RATS’ SUBMANDIBULAR SALIVARY GLANDS AFTER INTRODUCTION OF PROZERINE - Chaikovsky, Yu.B.; Tsukanov, D.V. (World of Medicine and Biology, 2012)
Determination of basic structural changes is in-process conducted in the lobules of submandibular salivary gland of rats after introduction of prozerine. It is set that prozerine influences on all phases of secretory process in the submandibular salivary glands of rats. Secret-formattion and secret-extrusion increases in end-pieces. In the ductal system active carry of liquid flags came to lumens from a vascular rate and periductal interstitium in the extended lumens. The spasm of capacitance-resistance link was determined in a haemomicrovascular rate, dilatation and plethora - in a capacity link.